ION MICROPROBE STUDIES OF EFREMOVKA CAIS: II. POTASSIUM ISOTOPE COMPOSITION AND 41CA IN THE EARLY SOLAR SYSTEM - Srinivasan G.; Sahijpal S.; Goswami J.N.; Ulyanov A.A. (My University, 1996)
The potassium isotope composition of refractory phases in Efremovka CAIs has been measured by an ion microprobe. Extensive studies of terrestrial standards were carried out to ensure that the experimental procedures adopted for potassium isotope studies provide accurate 41K/ 39K ratios of the analysed phases. Excess 41K is found to be present in refractory phases with high Ca/K ratios (>3 × 10 5) in all the four Efremovka CAIs analysed in this study. The excess 41K in these phases correlates well with their 40Ca/ 39K ratios. Several possible causes for this excess have been considered and it is concluded that in situ decay of 41Ca can best explain our observations. The results obtained in this work substantiate the conclusion drawn from our initial study (Srinivasan et al., 1994) and confirm the presence of the short-lived nuclide 41Ca (τ ~ 0.15 Ma) in the early Solar System with an initial 41Ca/ 40Ca value of (1.41 ±0.14) × 10 -8 at the time of formation of the Efremovka CAIs. We have considered several processes that may lead to the presence of 41Ca in the early Solar System. These include, production by energetic particles from an active early Sun, low energy particle induced reactions in a molecular cloud complex of which the proto-solar cloud was a part and freshly synthesized material from suitable stellar source(s). The last alternative turns out to be the best one from plausibility considerations. The Efremovka CAIs with excess 41K also have excess 26Mg that can be attributed to the decay of the short-lived nuclide 26Al(τ ~ 1 Ma) within these objects. The presence of both 26Al and 41Ca in Efremovka CAIs is used to infer the most probable stellar site(s) for the synthesis of these nuclides in a self consistent manner. Our observations coupled with predicted stellar production rates suggest an asymptotic giant branch (AGB) star to be a plausible source. However, we cannot completely rule out a supernova or a Wolf-Rayet star as being responsible for the synthesis and subsequent injection of these nuclides to the solar nebula. In spite of this inability to pinpoint the exact stellar source, our result constrains the time interval between the injection of freshly synthesized 41Ca and 26Al to the solar nebula and the formation of first Solar System solids (CAIs) to less than a million year.